Demonstration of Nuclear Immunofluorescence in Rift Valley Fever Infected Cells - Swanepoel, R.; Blackburn, N. K. (Journal of General Virology, 1977)
SUMMARY Eosinophilic intranuclear filaments described previously in Rift Valley Fever infected cells, were shown to fluoresce specifically in an indirect technique with antiserum to the virus. Actinomycin D failed to suppress development of the filaments or replication of the virus.